Integrated Access to Hybrid Information Resources - Sadeh, Tamar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
This paper is entitled "Integrated access to hybrid information resources", but integrated access is just a means to reach an end. Our challenge is to create an integrated environment in a heterogeneous world. Users are not aware, and do not want to be aware, of the differences between the various information resources that their institution provides. All they want is to be able to attain the information they are looking for, in the simplest and most straightforward way possible.